2007
DOI: 10.1161/atvbaha.107.143909
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1

Abstract: Objective-Nitrate tolerance is likely attributable to an increased production of reactive oxygen species (ROS) leading to an inhibition of the mitochondrial aldehyde dehydrogenase (ALDH-2), representing the nitroglycerin (GTN) and pentaerythrityl tetranitrate (PETN) bioactivating enzyme, and to impaired nitric oxide bioactivity and signaling. We tested whether differences in their capacity to induce heme oxygenase-1 (HO-1) might explain why PETN and not GTN therapy is devoid of nitrate and cross-tolerance. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…In animals, PETN was even reported to prevent endothelial dysfunction and atherogenesis in animal models of atherosclerosis. 81 The peculiar properties of this drug, including its capacity to induce the antioxidant defense protein heme oxygenase-1 and to increase the expression and production of ferritin, of the antioxidant molecule bilirubin, and of the vasodilator carbon monoxide 82 have been investigated recently by our group 83,84 ( Figure 8). …”
Section: Are All Nitrates Homogeneous In the Induction Of Tolerance Amentioning
confidence: 99%
“…In animals, PETN was even reported to prevent endothelial dysfunction and atherogenesis in animal models of atherosclerosis. 81 The peculiar properties of this drug, including its capacity to induce the antioxidant defense protein heme oxygenase-1 and to increase the expression and production of ferritin, of the antioxidant molecule bilirubin, and of the vasodilator carbon monoxide 82 have been investigated recently by our group 83,84 ( Figure 8). …”
Section: Are All Nitrates Homogeneous In the Induction Of Tolerance Amentioning
confidence: 99%
“…PETN protects against endothelial dysfunction and vascular oxidative stress, largely via HO-1-dependent mechanism. [10][11][12][13][14][15] In this study, we provided novel evidence that upregulation of the antioxidant enzyme HO-1 contributed to PETN-mediated cytoprotective effect by inhibiting mitochondrial ROS generation and NOX4 expression. Previous studies have reported that NOX4-dependent O 2…”
Section: Discussionmentioning
confidence: 75%
“…10,11 PETN has been shown to protect against endothelial dysfunction and vascular oxidative stress. [12][13][14][15] Potential effects of PETN treatment in congestive heart failure (CHF) have not been studied yet. Therefore, we investigated the effects of long-term treatment with PETN on progressive cardiac remodeling (dilation and cellular and molecular dysregulations) in CHF rats after extensive myocardial infarction (MI).…”
mentioning
confidence: 99%
“…We employed the L-012 ECL assay for measuring mitochondrial peroxynitrite formation in nitrate tolerance induced by nitroglycerin in rats [39,[112][113][114][115][116][117] or mice [56,118,119]. In these publications L-012 ECL signals correlated well with 3-nitrotyrosine levels in mitochondria of various tissues upon in vitro and in vivo nitroglycerin treatment, with ROS and RNS detection by other assays such as HPLC-based 2-hydroxyethidium measurement or dihydrorhodamine fluorescence, inhibition of the redox-sensitive enzyme mitochondrial aldehyde dehydrogenase (ALDH-2) and other markers of oxidative stress such as products of lipid peroxidation or 8-oxo-G and was improved by various antioxidant therapies (reviewed in [120]).…”
Section: L-012-based Whole Blood Chemiluminescence Assay (L-012 Oxidamentioning
confidence: 99%